Penn classification in acute aortic dissection patients. Issue 2 (1st April 2016) - Pisano, Calogera; Balistreri, Carmela Rita; Torretta, Federico; Capuccio, Veronica; Allegra, Alberto; Argano, Vincenzo; Ruvolo, Giovanni
Abstract : Objective The objective of this study was to evaluate the effectiveness of the Penn classification in predicting in-hospital mortality after surgery in acute type A aortic dissection patients. Methods We evaluated 58 patients (42 men and 16 women; mean age 62.17 ± 10.6 years) who underwent emergency surgery for acute type A aortic dissection between September 2003 and June 2010 in our department. We investigated the correlation between the pre-operative malperfusion and in-hospital outcome after surgery. Results Twenty-eight patients (48%) were Penn class Aa (absence of branch vessel malperfusion or circulatory collapse), 11 (19%) were Penn class Ab (branch vessel malperfusion with ischaemia), 5 (9%) were Penn class Ac (circulatory collapse with or without cardiac involvement) and 14 (24%) were Penn class Abc (both branch vessel malperfusion and circulatory collapse). The number of patients with localized or generalized ischaemia or both, Penn class non-Aa, was 30 (52%). In-hospital mortality was 24%. In-hospital mortality was significantly higher in Penn class Abc and Penn class non-Aa. Intensive unit care stay, hospital ward stay and overall hospital stay was longer in Penn class non-Aa vs Penn class Aa. De Bakey type I dissection and type II diabetes mellitus were associated with in-hospital mortality. Conclusion Preoperative malperfusion is important for the evaluation of patients with acute aortic type A dissection. The Penn classification is a simple and quick method to apply and predict in-hospital mortality and outcomes.